2005
DOI: 10.1002/j.2162-6057.2005.tb01255.x
|View full text |Cite
|
Sign up to set email alerts
|

Creativity, Originality, and Appropriateness: What do Explicit Instructions Tell Us About Their Relationships?

Abstract: Originality is a necessary part of creativity, but creative things are more than just original. They also solve a problem, or more generally are somehow fitting or appropriate. Yet previous research found an inverse relationship between ratings of originality and ratings of appropriateness. The present investigation employed a different methodology — it focused on the generation of ideas instead of judgments about them — to reexamine the relationships between originality, appropriateness, and creativity. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(110 citation statements)
references
References 12 publications
7
100
0
3
Order By: Relevance
“…For both measures the results showed that instructions lead to different results based on the two tasks that participants were instructed to complete. These results indicate that instructions play a significant role in the way different images are interpreted, a claim that is supported by previous research on the influence of instructions on divergent production (Runco, Illies, & Eisenman, 2005). The role of instructions for perceptual switching needs to be addressed more thoroughly by future research.…”
Section: Discussionsupporting
confidence: 70%
“…For both measures the results showed that instructions lead to different results based on the two tasks that participants were instructed to complete. These results indicate that instructions play a significant role in the way different images are interpreted, a claim that is supported by previous research on the influence of instructions on divergent production (Runco, Illies, & Eisenman, 2005). The role of instructions for perceptual switching needs to be addressed more thoroughly by future research.…”
Section: Discussionsupporting
confidence: 70%
“…So today people will work on a few different creativity tasks, which look at how people think creatively.‖ We think that it is essential to instruct people to try to be creative, for three reasons. First, instructing people to be creative increases the creativity of their responses (e.g., Christensen et al, 1957;Runco, Illies, & Eisenman, 2005), which will raise the ceiling of creativity in the sample and hopefully expand the variance in creativity scores. Second, instructing people to be creative makes the scores more valid indicators of individual differences.…”
Section: Education (8%) and Psychology (8%) Divergent Thinking Tasksmentioning
confidence: 99%
“…Определили смо се да укључимо овај тест зато што је оригиналност саставни део креативности (Runco et al, 2005). Тест се састоји од 38 тврдњи.…”
Section: варијабле и инструментиunclassified